EFFECT OF SOME AMINO ACIDS ON TILLERING AND YIELD OF THREE BREAD WHEAT CULTIVARS - & Al-Naqeeb, Baqir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to investigate the effect of some amino acids on tillering and grain yield of bread wheat cultivars. A field experiment was carried out at the agricultural experiment station, College of Agriculture Engineering Sciences, University of Baghdad during the two winter seasons, 2016-2017 and 2017-2018. Randomized Complete Block Design within split plots arrangement was used in three replicates. The experiment included two factors, the first (main plots) was the wheat cultivars (IPA 99, Buhooth 22, and Abu-Graib3) and the second (sub-plots) was foliar application three amino acids (L-Tryptophan, L-Glycine, and L-Lysine) with concentrations 50 and 100 mg L-1 and the amino acid L-Cystine at 100 and 150 mg L-1 and control treatment. The treatments of foliar application were applied during two growth stages, the first was when the main stem had three leaves (ZGS: 13) and the second was when the plant entered the flowering stage (ZGS: 60). Results showed the significant superiority of Buhooth 22 in most growth traits, which produced the highest number of tillers.m-2 (556.30 and 568.15 tillers m-2), number of spikes (476.74 and 494.19 spikes m-2), weight of 1000 grains (31.09 and 32.43 g), and grain yield (5.39 and 5.15 Mg ha-1) for the two seasons respectively. The treatment of foliar application L-Tryptophan at 50 mg L-1 was significantly superior in most traits of yield components which produced the highest values of the number of tillers (616.89 and 627.78 tillers m-2), number of spikes (477.00 and 944.67 spikes m-2), weight of 1000 grains (32.01 and 33.55g), and grain yield (5.77 and 5.33Mg ha-1) in the two seasons, respectively. The response of wheat cultivar growth and yield to amino acids differed significantly.